Strategi Pengelolaan Usaha Tambak Ikan Bandeng Secara Berkelanjutan Di Kecamatan Sedati, Kabupaten Sidoarjo - Anna Nafiah Karimatus Sholikhah; Abdul Wahib Muhaimin; Sivana Maulidah; Agus Tjahjono (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Milkfish farming is a vital sector in supporting the local economy and the well-being of coastal communities. This study aims to formulate sustainable management strategies for milkfish farming in Sedati Subdistrict, Sidoarjo Regency. The research employs a multidimensional approach using Multi-Dimensional Scaling (MDS), prospective analysis, and I/D Matrix mapping to identify existing conditions and design sustainability strategies. The results indicate that the sustainability of milkfish farming enterprises can be enhanced through an integrative approach encompassing institutional strengthening, the application of eco-friendly technologies, product diversification, and government policy support. These strategies are expected to promote economic, ecological, and social sustainability while contributing to the achievement of the Sustainable Development Goals (SDGs).